PENYULUHAN DAN EDUKASI PENYAKIT HIPERTENSI PADA POSYANDU LANSIA SEMI WREDA, YOGYAKARTA - Noviani, Desi; Rahmi Windhy Astari, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Hypertension, a chronic condition that usually attacks someone over the age of 18 years which is characterized by an increase in blood pressure on the walls of the arteries and makes the heart work harder to pump blood throughout the body through blood vessels. The risk of developing hypertension is higher in the elderly because the risk of developing hypertension increases with age. Upaya that can be done to increase the knowledge of the elderly about hypertension is by providing health education directly or through leaflets, to provide information about hypertension and how to prevent it. Good health education can help the elderly understand risk factors, symptoms, complications, and appropriate treatment methods. Making healthy habits such as reducing salt consumption and eating healthy foods that are low in fat and high in fiber can help control blood pressure. Avoiding smoking and drinking alcohol excessively can also help prevent hypertension and improve overall health. Supportand motivation are very important for the elderly who suffer from hypertension. Support and motivation from family, friends, doctors, and support groups can help seniors better manage hypertension and improve their quality of life. By making these efforts, it is hoped that the elderly can have better knowledge about hypertension, and can manage and prevent the disease better as well.